Formação para a atenção primária à saúde: um estudo de caso da turma de profissionais de Educação Física do curso de especialização em atenção básica em saúde da família da UFMG - Denise Mourao Falci (2013)
The recent entry of Physical Education Professional in Primary Health Care, especially after its insertion into the Support Center for Family Health, showed his fragile training for this context. This study aimed to analyze a training strategy of the Physical Education Professional for its insertion in Primary Health Care, considering the following specificobjectives: to describe the trajectory of Physical Education Professional in primary care, to identify the challenges faced by them at this level of care and to analyze their training for the Primary Health Care. This is a qualitative exploratory study of case study. Different instruments were used for data gathering: documentary research, focus groups and semistructured interview. In the documentary research, scientific articles, books, dissertations and both government and institutional documents have been used. From the documentary research was historically contextualized the insertion of Physical Education in primary care with anemphasis on their training for this field. Two focus groups were conducted among 15 bachelors in Physical Education, students of the Specialization Course in Primary Care Family Health / UFMG. The semi structured interviews were conducted individually with the following key informants: one representative of the coordination of the specialization course mentioned, one representative of the Undergraduate course in Physical Education/ UFMG and one representative of the presidency of the Regional Council of Physical Education, 6th Region / Minas Gerais. Data were analyzed through content analysis, resulting in the following categories: integration into Primary Health Care; training for Primary Health Care and difficulties. It was possible to show that the insertion of Physical Education Professional in this field is recent and positive, and was mentioned as a paradigm shift for the profession. However, individuals stated that training is insufficient for their performance in primary care, revealing the need for curricular changes and identifying undergraduation as an important strategy to reduce this deficiency. In this context, the Specialization Course in Primary Care in Family Health was identified as an important strategy for the training of Physical EducationProfessional. Its continuity and expansion were suggested. Difficulties, resistance in joining the teams, the lack of definition of the functions and the lack of a goal plan were reported. It was concluded that the inclusion of the recent Physical Education Professional in primary brought positive expectations, but the fragile undergraduate training for primary care hinders their integration in this area, which leads to the need for implementation of strategies that are consistent with the principles and guidelines of Brazilian Health System.